2023
DOI: 10.3390/gels9110916
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Safranin O Dye by Alginate/Pomegranate Peels Beads: Kinetic, Isotherm and Thermodynamic Studies

Amina Abbaz,
Sihem Arris,
Gianluca Viscusi
et al.

Abstract: Water pollution is regarded as a dangerous problem that needs to be resolved right away. This is largely due to the positive correlation between the increase in global population and waste production, especially food waste. Hydrogel beads based on sodium alginate (Alg) and pomegranate fruit peels (PP) were developed for the adsorption of Safranin O dye (SO) in aqueous solutions. The obtained Alg−PP beads were widely characterized. The effects of the contact time (0–180 min), initial concentration (10–300 mg/L)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…The first group analysed (adsorption reaction models) includes the pseudo-first-order, pseudo-second-order, and Elovich models [ 59 , 60 ]. For the adsorption diffusion models, the following were calculated: liquid film diffusion model, intraparticle diffusion model (Weber–Morris model and Bangham and Burt model) [ 61 , 62 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first group analysed (adsorption reaction models) includes the pseudo-first-order, pseudo-second-order, and Elovich models [ 59 , 60 ]. For the adsorption diffusion models, the following were calculated: liquid film diffusion model, intraparticle diffusion model (Weber–Morris model and Bangham and Burt model) [ 61 , 62 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Due to high magnetic saturation, minimal toxicity and biocompatibility, superparamagnetic iron oxide (Fe3O4) nanoparticles have emerged as a promising candidate for various applications in modern technologies [9]. Several research groups have reported the decontamination of the wastewater from SO dye by using various types of adsorbent materials [10][11][12][13][14][15]. However, SO dye removal efficiency was found less effective with all these reported adsorbent materials.…”
Section: Introductionmentioning
confidence: 99%